EMP3 is induced by TWIST1/2 and regulates epithelial-to-mesenchymal transition of gastric cancer cells - Ming Han; Wanpeng Xu (Tumor Biology)
In this study, we aimed to explore new downstream effectors of TWIST1/2 in inducing epithelial-to-mesenchymal transition in gastric cancer. Bioinformatic data mining was performed using data in The Cancer Genome Atlas Stomach Adenocarcinoma. Survival curves were generated using Kaplan–Meier plotter. Gastric cancer cell lines (AGS and SGC-7901) were used as in vitro cell model to investigate the regulative effect of TWIST1/2 on epithelial membrane protein 3 expression and the progression of epithelial-to-mesenchymal transition. Results showed that TWIST1 and TWIST2 are usually co-upregulated in patients with primary gastric cancer. High TWIST1 expression is associated with worse overall survival (hazard ratio = 1.26; 95% confidence interval = 1.06–1.49; p = 0.007) and also worse first progression-free survival (hazard ratio = 1.47; 95% confidence interval = 1.18–1.82; p < 0.0001). Similarly, high TWIST2 expression is associated with unfavorable overall survival (hazard ratio = 1.71; 95% confidence interval = 1.32–2.22; p < 0.0001) and progression-free survival (hazard ratio = 1.99; 95% confidence interval = 1.45–2.72; p < 0.0001). Epithelial membrane protein 3 is negatively correlated to CDH1 expression (Pearson’s r = −0.46) but is positively correlated to VIM expression (Pearson’s r = 0.83). Knockdown of epithelial membrane protein 3 significantly increased E-cadherin but significantly decreased Vimentin expression in AGS cells. Gastric cancer patients with metastasis have significantly higher epithelial membrane protein 3 expression than the cases without metastasis. In addition, high epithelial membrane protein 3 expression is associated with worse overall survival (hazard ratio = 2.59; 95% confidence interval = 2.06–3.26; p < 0.0001) and also worse progression-free survival (hazard ratio = 2.21; 95% confidence interval = 1.78–2.74; p < 0.0001). In conclusion, epithelial membrane protein 3 is a downstream effector of TWIST1/2 in inducing epithelial-to-mesenchymal transition in gastric cancer. Epithelial membrane protein 3 upregulation might be associated with gastric cancer metastasis and is a potential indicator of unfavorable overall survival and progression-free survival in gastric cancer patients.